Past and Present A Victorian View of War - Beardsley, Christina (2005)
Features the experience of preacher Frederick William Robertson in the Kaffir Wars in South Africa in the 19th century. Interest of Robertson to become a soldier; Challenges encountered by Robertson during the war; Opinion of Robertson on freedom and foreign intervention.
Keywords: FRONTIER Wars, South Africa, 1779-1878; Intervention (International law); Liberty; ROBERTSON, Frederick William, 1816-1853; South Africa; War